Experience of Caring as Source of Abductive Reasoning in Nursing: a Pragmatic Vision - Soto Lesmes, Virginia Inés; Ramírez Niño, Jaime Alberto; Bueno-Robles, Luz Stella (Investigación y Educación en Enfermería, 2023)
The aim of this reflection article consists in proposing a methodology that makes visible the epistemic practice through abductive reasoning for the generation of knowledge from an experience of caring. For such, the work describes the connections between the science of nursing and inter-modernism, develops the idea of the nursing practice as source of knowledge, and defines the components of abductive reasoning for the practice. Finally, the work presents an academic exercise developed within the framework of the assignment Evaluation of the theory for research and practice in the PhD program in nursing at Universidad Nacional de Colombia on how a theory was developed from a situation of care and its scientific usefulness upon generating in patients a sense of fullness in their health and in nursing professionals, satisfaction with their work.